Tsunami and Earthquake Warning Systems - Ishiwatari, Mikio (World Bank, Washington, DC, 2013)
Warning systems can mitigate the damage caused by tsunamis and other natural events, and prevent the loss of human life and properties. Countermeasures, such as evacuations to higher ground and the stopping of trains, depend on getting the right information and disseminating it in a timely manner. Warning systems must also be aligned with community response. While Japan has developed the most sophisticated tsunami-warning system in the world, the system underestimated tsunami height on March 11 and may have misled the evacuees and increased human losses. This report gives findings; lessons; and recommendations for developing countries.